Modification, Commodification Of The Dance Of Sekapur Sirih As The Cultural Identity Of The City Of Bengkulu - Agustina, Agustina; Erlinda, Erlinda; Kadir, Ernida; Sriwulan, Wilma (LPPM Institut Seni Indonesia Padangpanjang, 2024)
The study aims to investigate the modification, commodification of Sekapur Sirih dance as the identity of Bengkulu City. To refresh its attractiveness, the dance underwent modifications of the dance elements of its movement, duration, and musical components with the support of the government and artists. In addition, the commodification of cultural products occurs in Sekapur Sirih dance, which is carried out by artists and communities in an effort to increase commercial value as a form of source of income. Production, distribution, and consumption are part of the process of turning traditional art into high-value commodities. The research method used is qualitative, with data collection techniques of observation, interviews, and documentation. The theoretical paths used are modification (Shils Hand), commodification (Vicent Mosco), and identity. (Yasraf Amir Piliang). The results of the research showed that the modifications carried out reflected the identity of Bengkulu City that appeared in the movement of Sekapur Sirih dancing and the commodification made into cultural products packaged to commercial value, meaning that packaging not only enhances cultural value but also requires economic value.